2021
DOI: 10.1021/jacs.1c06212
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modifications of Ag Catalyst Surfaces with Imidazolium Ionomers Modulate H2 Evolution Rates during Electrochemical CO2 Reduction

Abstract: Bridging polymer design with catalyst surface science is a promising direction for tuning and optimizing electrochemical reactors that could impact long-term goals in energy and sustainability. Particularly, the interaction between inorganic catalyst surfaces and organic-based ionomers provides an avenue to both steer reaction selectivity and promote activity. Here, we studied the role of imidazolium-based ionomers for electrocatalytic CO 2 reduction to CO (CO 2 R) on Ag surfaces and found that they produce no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 55 publications
2
51
1
Order By: Relevance
“…50 Similarly, Koshy et al noted that imidazolium-based ionomer coatings have no effect on CO 2 R activity but are able to modulate the activity for HER on Ag. 51 These studies suggest that while some of the ionomer effects we have observed are transferable to Ag, the details of these effects may be chemistrydependent. Further work is needed to explore how ionomers can affect the CO 2 R electrocatalyst microenvironment.…”
mentioning
confidence: 78%
“…50 Similarly, Koshy et al noted that imidazolium-based ionomer coatings have no effect on CO 2 R activity but are able to modulate the activity for HER on Ag. 51 These studies suggest that while some of the ionomer effects we have observed are transferable to Ag, the details of these effects may be chemistrydependent. Further work is needed to explore how ionomers can affect the CO 2 R electrocatalyst microenvironment.…”
mentioning
confidence: 78%
“…69 As the most frequently used anions, HCO 3 − can serve as the supplementary proton donor for the reduction reaction beyond protons or water, in which the undesired HER could be promoted. 88,89 In some cases, HCO 3 − also provided the carbon reactant for the CO 2 RR when it is close to the reaction interface. 90 Moreover, halide anions abundant in sea water (environmentally friendly electrolyte) have also demonstrated their functions in adjusting the activity and selectivity of the CO 2 RR on account of their strong interaction with the metal surface.…”
Section: Robust Strategies For Boosting the Energy Efficiency Of The ...mentioning
confidence: 99%
“…Novel materials/properties/phenomena are assessed with respect to the contemporary literature, and a new theory is then proposed. [10,[28][29][30][31] Nowadays, combining experimental and theoretical studies has proven successful in elucidating reaction mechanisms of some electrochemical transformations (e.g., water to hydrogen and oxygen, carbon dioxide to valuable carbon-based products, or nitrogen to ammonia), which provide rational guidance toward the development of application-driven catalysts. [27,[32][33][34][35] For both design approaches, building a novel material is a must-do step, and a suitable synthesis method is one of the pivotal elements to dictate the output properties of the most promising catalyst with respect to an intrinsic activity or long-term stability.…”
Section: Catalyst Design Strategiesmentioning
confidence: 99%